Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

Gender and economic growthin Kenya: unleashing the power of women - Ellis, Amanda; Cultura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (The World Bank, 2007)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, “Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment,” this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya’s Economic Recovery Strategy for Wealth and Employment Creation 2003–2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; gender / género; justice / justiça